Assembling the Current Pieces: The Puzzle of RNA-Mediated Regulation in Staphylococcus aureus - Barrientos, Laura; Mercier, Noémie; Lalaouna, David; Caldelari, Isabelle (Frontiers in Microbiology, 2021)
The success of the major opportunistic human Staphylococcus aureus relies on the production of numerous virulence factors, which allow rapid colonization and dissemination in any tissues. Indeed, regulation of its virulence is multifactorial, and based on the production of transcriptional factors, two-component systems and regulatory RNAs (sRNAs). Advances in high throughput sequencing technologies have unveiled the existence of hundreds of potential RNAs with regulatory functions, but only a fraction of which have been validated in vivo. These discoveries have modified our thinking and understanding of bacterial physiology and virulence fitness by placing sRNAs, alongside transcriptional regulators, at the center of complex and intertwined regulatory networks that allow S. aureus to rapidly adapt to the environmental cues present at infection sites. In this review, we describe the recently acquired knowledge of characterized regulatory RNAs in S. aureus that are associated with metal starvation, nutrient availability, stress responses and virulence. These findings highlight the importance of sRNAs for the comprehension of S. aureus infection processes while raising questions about the interplay between these key regulators and the pathways they control.